Tax expenditures jako instrument polityki podatkowej - Wyszkowski, Adam (Tax Expenditures as a Tax Policy Instrument, 2011)
Tax policy as a part of fiscal policy is an important instrument in a state activity. Taxes and other fiscal burden are used by government to change tax-payers behaviour in consumption, savings and activity. One of the tax policy instruments are tax expenditures generally understood as tax provisions that allow certain groups of people to pay less taxes. Tax expenditures substitute direct budget expenditures in fiscal policy. At a time when many government budgets have debt, there is pressure to avoid inefficient government programmes. That is why it is important to identify all expenditures and verify them using efficiency criteria. One of the goals of tax expenditures analyses is to compare them to direct expenditures and choose more effective way to subside benefits of state budget.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 167, s. 542-552
Keywords: polityka podatkowa; tax expenditures; preferencje podatkowe